PERCEIVED AVAILABILITY OF DRUG USE IN ONE’S COMMUNITY AND PERCEIVED DRUG USE IN THE COMMUNITY AMONG UNIVERSITY STUDENTS 2016 - Dini Mulyati; Susheewa Wichaikull; Yupaporn Tirapaiwong (Fakultas Keperawatan-Universitas Syiah Kuala, 2020)
Drug use is the major problem worldwide, particularly in adolescence and early adulthood. The objective of this study was to examine the relationships between perceived availability of drug use in one’s community, perceived drug use in the community, and drug use among university students. A cross sectional study was conducted with 382 students which are recruited form 2 of 7 public universities and 3 of 10 private universities in Aceh, Indonesia. Simple random sampling method was used to select the participants. Data were collected by self-administered questionnaires. Data were analyzed using descriptive statistics and Chi-square test. The prevalence of drugs user was 31.6%. The results of this study revealed that perceived availability of drug use (c² = 106.711, p .001) and perceived drug use in the community (c² = 31.255, p .001) were significant related with drug use (tobacco products, methamphetamine, and marijuana). Based on these findings, health care provider and sectors of universities should be concerned about drug use behavior and seek appropriate strategies to promote healthy behavior and to reduce its prevalence.Keywords: Drug use; Community; Aceh;